Left ventricular systolic dysfunction potentially contributes to the symptoms in heart failure with preserved ejection fraction. Issue 10 (1st October 2019) - Guan, Zhengyu; Liu, Shuang; Wang, Yonghuai; Meng, Pingping; Zheng, Xianfeng; Jia, Dalin; Yang, Jun; Ma, Chunyan
Abstract: Aims: Left ventricular diastolic dysfunction (LVDD) is considered a key factor associated with heart failure (HF) symptoms in patients with preserved ejection fraction (HFpEF). However, LV systolic performance, including LV systolic function and synchrony, has not been well characterized in these patients. The aims of this study were to assess to investigate the underlying relationship and differences between subclinical LVDD and HFpEF. Methods: Eighty‐six patients with LVDD were recruited (58 with HFpEF and 28 with subclinical LVDD). Systolic left ventricular (LV) longitudinal strain (LS), systolic longitudinal strain rate (LSrS), early diastolic longitudinal strain rate (LSrE), and late diastolic longitudinal strain rate (LSrA) were measured using speckle tracking echocardiography. LV diastolic and systolic dyssynchrony (Te‐SD and Ts‐SD) were calculated. Forty age‐ and sex‐matched healthy individuals were enrolled as a control group. Results: LV global LS and LSrS were decreased in patients with HFpEF than in normal controls and subclinical LVDD patients ( P < .05). Te‐SD and Ts‐SD were significantly more prolonged in subclinical LVDD and HFpEF patients than in the control group ( P < .05). Reduced LS was associated with HF symptoms in LVDD patients, and a cutoff value of −18% for LS could differentiate HFpEF from subclinical LVDD with 73% sensitivity and 69% specificity. Conclusion: LV systolic function and mechanical dyssynchrony were impaired in HFpEF patients. Deteriorated LV longitudinal systolic function was likely correlated with the symptoms of HFpEF.